Pelatihan Penulisan Artikel Ilmiah Untuk Dosen Dan Mahasiswa - Kurniawati, Ria; Khusaini, Khusaini; Latuconsina, Hudaya; Atrisia, Marchela Indah (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The value added of a university is strongly influenced by the high or low number of studies. But unfortunately, the interest of lecturers and students in writing scientific articles is still low. This training activity aims to improve the research and publication skills of lecturers and students. This activity was attended by 134 participants consisting of lecturers and students. Methods of implementing activities include the stages of preparation, implementation, evaluation, and reporting. The training implementation technique is carried out online. The results of this training activity showed that the participants were quite satisfied with this activity. During the activity the participants actively participated in discussion activities. This activity is able to contribute to lecturers and students to improve the quality of research and scientific publications in Higher Education.